2015
DOI: 10.1213/ane.0b013e318292ed45
|View full text |Cite
|
Sign up to set email alerts
|

Leaving More Than Your Fingerprint on the Intravenous Line

Abstract: Introduction Acute care handling of IV stopcocks during anesthesia and surgery may result in contaminated IV tubing sets. In the context of widespread propofol use, a nutrient-rich hypnotic drug, we hypothesized that propofol anesthesia increases bacterial contamination of IV stopcocks and may compromise safety of IV tubing sets when continued to be used after propofol anesthesia. Methods We conducted an in vitro trial by collecting IV tubing sets at the time of patient discharge from same-day ambulatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…The most common reservoirs associated with extrinsic contamination of propofol are syringes or micro-droppers, vials, and IV stopcock dead space. Syringes or micro-droppers have been implicated in most outbreaks ( 23 – 27 ). Propofol vials have been demonstrated to be a reservoir for microbes when contents are exposed to the environment ( 28 ).…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most common reservoirs associated with extrinsic contamination of propofol are syringes or micro-droppers, vials, and IV stopcock dead space. Syringes or micro-droppers have been implicated in most outbreaks ( 23 – 27 ). Propofol vials have been demonstrated to be a reservoir for microbes when contents are exposed to the environment ( 28 ).…”
Section: Study Selectionmentioning
confidence: 99%
“…It is believed that administering a dose >200 mg to an adult in an OR will increase the probability of using an additional vial as a multi-dose vial for > 1 patients. IV stopcock dead space has been shown to provide a potential route of entry for pathogenic, multidrug-resistant bacteria in infusion lines ( 20 , 27 ).…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cole et al found that 12–16% of multi-use injection ports through which medications are administered contain bacteria within 6 h [23]. Crucially, Loftus et al have demonstrated an association between contamination of these ports and postoperative mortality [20] and transmission of pathogenic bacteria from one patient on an operating list to another, including transmission via the hands of providers and environmental surfaces [24].…”
Section: Introductionmentioning
confidence: 99%